College Students' Locus of Control in Relation to Their Socio-Family Environments: Influence of Family Environment on College Students' Locus of Control in the Indian Culture (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The social learning theory led to the development of the concept of internal control ofreinforcement as opposed to external control of reinforcement. The extent to which a person feels thatreinforcements are dependent on his or her actions is described by this hypothesis. The social learningtheory led to the development of the idea of internal control of reinforcement as opposed to externalcontrol of reinforcement. Internal control refers to the notion that a person's behaviour, ability, or traitwill determine whether or not they will get reinforcements.In relation to this specific aspect of locus of control, there are a number of studies on the subject thatcan be found in the literature of psychology. On the other hand, the large majority of the studies that arerelevant to this subject have generally been conducted in a cultural environment that is different fromthat of our own. This is the case the majority of the time. As a result of this, the purpose of the currentstudy is to investigate the extent to which socio-familial factors such as family type, family size, birthorder, socio-economic status, and parental rearing behaviours can be used for interpreting the originand growth of an internal versus an external locus of control in the Indian culture. Specifically, theresearch will focus on the Indian culture. As a result, the purpose of this study is to make an effort todiscover and comprehend the many drivers that have an impact on the social and familial aspects thatdetermine the locus of control of college students. After pursuing the literature survey, it is found thatInternal-oriented college students characterised their parents as Warm, consistent, and encouragingchildren to regulate their own reinforcing (achievement pressure). Their parents used strategies thatconvey the sense of external control, such as over-protection, loss of privileges, and emotionalpunishment.